Who Are the Stalking Victims? Exploring the Victimization Experiences and Psychosocial Characteristics of Young Male and Female Adults in Hong Kong - Chan, Heng Choon (Oliver) (Journal of interpersonal violence, 2021)
Most stalking studies are conducted in the West. Limited information is available on victims of stalking from the Asian continent. This study specifically explored the victimization experiences of young male and female adults in Hong Kong. Using a large sample of university students (N = 2,496) aged between 18 and 40 years, the gender distribution of stalking incident characteristics was examined, along with prevalence of various stalking behaviors, and victim–offender relationships by types of stalking behaviors. The differential role of demographic and psychosocial characteristics in stalking victimization experience was also explored. The lifetime prevalence rate of stalking victimization was 8.2%, with a higher estimate in females than males (11.6% vs. 3.8%). The sample analyzed in this study was 196 stalking victims. Although surveillance-oriented behaviors were most frequently reported by both males and females, significant gender differences in types of stalking behaviors were noted. Multivariate analyses indicated that increases in age and levels of self-esteem were correlated with an increased probability of experiencing stalking victimization, while being a male and higher levels of life satisfaction were related to a lower likelihood of falling prey to stalking victimization. This study concludes with a call for anti-stalking legislation in Hong Kong given the devastating nature and consequences of stalking victimization.